Sexual health indicators for the United States: Measuring progress and documenting public health needs - Ford, Jessie V.; Ivankovich, Megan B.; Coleman, Eli (Frontiers in Public Health, 2023)
Introduction Today, we are facing increased and continued adverse sexual health outcomes in the United States, including high post-COVID-19 pandemic rates of sexually transmitted infections (STIs). For the past 20 years, there have been calls for a national health strategy and a more comprehensive sexual health approach to address the myriad of persistent sexual health problems in this country. Employing a sexual health approach requires shifting from a longstanding, stigmatizing focus on morbidity toward a holistic and integrated focus on health rather than disease. While strategies are being implemented by multisectoral stakeholders, it is also important to establish a core set of indicators that broadly describe the state of sexual health in the U.S. and allow for measurement across time. The development of a comprehensive scorecard with key sexual health indicators has been proposed by other entities (e.g., Public Health England, World Health Organization), but such an attempt has not been made in the U.S. Methods A review of national U.S. surveys and surveillance systems with items related to sexual health was conducted for years 2010–2022 to develop an inventory of existing data that yield national estimates for potential indicators of sexual health. Results We selected 23 sexual health indicators in four broad domains including: (1) knowledge; communication and attitudes (five indicators); (2) behaviors and relationships (four indicators); (3) service access and utilization (seven indicators); and (4) adverse health outcomes (seven indicators). Recent data for each indicator are provided. Discussion A growing body of evidence shows the positive effects of moving away from a morbidity focus toward an integrated, health-promoting approach to sexual health. Yet, not much has been done in terms of how we implement this national shift. We argue that measurement and monitoring are key to future change. We envision these core sexual health indicators would be published in the form of an index that is publicly available and updated frequently. These sexual health indicators could be used for ongoing monitoring, and to guide related research, programming, and policy development to help promote sexual health in coming years.